Proyecto de factibilidad para la creación de una empresa productora de lámparas rústicas de madera y su comercialización en la ciudad de Loja - Ojeda Astudillo, Johanna Cristina (2015)
This thesis project aims primarily to determine the feasibility of creating a manufacturer of rustic wooden lamps and marketed in the city of Loja, for which the five major studies were performed which is formed a feasibility project such as: market research, technical study, organizational study, economic study and financial evaluation. For the development of research methods used: deductive, inductive, analytic, synthetic, descriptive, mathematical and statistical, which provided the mechanisms to undertake the activities in the stages of the development of the thesis. So the survey technique applied to the study population covering the urban household in the city of Loja and companies that sell lamps in the city, of which important information was acquired for the development of was also used market study. In this study an effective demand of 24.104 lamps for the first year of establishment of the company, value representing 90% acceptance by families that buy rustic lamps was established, with an average annual purchase per family two lamps. It supplies where few companies in the city of Loja that sell rustic lamps, earning an average annual sales of 720 lamps are also identified. Getting an unmet demand for 23.384 rustic lamps, which shows that there is great demand for the product on the market, but there is not enough supply to cover it. On the technical study the size of the project, with an installed capacity of 100% of 2.880 annual lamps, and a capacity utilization for the first year of production of 75% of 2.160 lamps are determined. The location and physical layout of the company was established; project engineering and corresponding to the description of the production process of the rustic lamps and resources necessary for their manufacture. As it regards the organizational study, a limited liability company, whose corporate name is settled, "LampRustic Cia. Ltda.” it will have a shelf life of 5 years. For the company to efficiently fulfill its activities, he established an administrative structure that allows for proper use of resources; for that hierarchical levels produced as well as the structural and functional flowcharts positional; in addition to the operating manuals for each position. As a result of previous studies, the economic study of the company was conducted, determining budgets of fixed assets, deferred assets and current assets; giving them required a total investment of $ 27.892,23, value that will be financed with equity partners and a credit granted by the National Development Bank. The projected total cost of production for the five-year life of the company, being the first year of $ 49.886,85, to which a unit production cost of $ 23,10 you get, value is assigned is also displayed a profit margin of 30%, resulting in a retail price of $ 30,02. Sales revenue for the first year will be $ 64.852,91, with a net profit (profit and loss) $ 8.930,25 and assuming the obligations of the utility workers, income tax and legal reserve. Breakeven for costs was classified into fixed and variable, resulting in the first year an installed capacity of 67,46%, and sales of $ 43.697,73, which at this point the company breaks even; but if these values are lower than the equilibrium point obtained, the company has losses and if they are older have utilities. Finally, the financial evaluation of the project was carried out, based on the cash flow obtained and establishing the different indicators that comprise it. On the Net Present Value (NPV) of $ 4.199,14 an outcome which is positive and greater than 1 was obtained, interpreting that the project is feasible because it creates value over the years. In the Internal Rate of Return (IRR) of 14,91%, which shows that the project should be accepted as the IRR is greater than the cost of capital is 10% was obtained. In the Capital Recovery Period (PRC), the project investment is recovered in three years, 8 months and 1 day. As for the cost / benefit ratio (RBC), for every $ 1 invested company, you will get $ 0,40 profit. With regard to sensitivity analysis, the project is accepted as it is not financially sensitive to the increase in costs up to 24,61%, as it is not sensitive to the decline in revenue to 17,61%. With all the information gathered and after the results of each of the studies information, it is concluded that the proposed project is profitable; as such its realization is feasible